NOVOS COMPLEXOS LUMINESCENTES MONO E BINUCLEARES DE COBRE(I) BASEADOS EM LIGANTES TIOCARBAMOIL-PIRAZOLINAS COM PROMISSORA APLICAÇÃO BIOLÓGICA FRENTE A BACTÉRIAS PATOGÊNICAS E CÉLULAS TUMORAIS - Cristiane Freitas de Almeida Teixeira (2021)
This work describes the synthesis, structural characterization, spectroscopic studies and biological activity of five copper (I) complexes based on pyrazolinic ligands, including two mononuclear and three binuclear compounds with the presence of co-ligand bis (diphenylphosphine) ethane. The complete characterization of such complexes included analytical techniques such as: infrared and UV-Vis spectroscopy, fluorescence, 1 H and 13 C nuclear magnetic resonance, high resolution mass spectrometry (HRMS), single- crystal X-ray diffractometry, CHN elemental analysis, melting point, in addition to TD- DFT calculations. The data from crystallography demonstrated the formation of mono and binuclear compounds with trigonal and distorted tetrahedral geometries around the copper (I) atom. The study of molecular absorption in the UV-Vis region showed maximum absorption bands in the regions of 230 and 329 nm, while luminescent behavior was presented in 315 and 550 nm complexes with maximum emission at 362 nm, after excitation at 300 nm. Structures and the purity were confirmed by IR spectroscopy, UV-Vis, 1H and 13C NMR, HRMS, elemental analysis and melting point. In vitro biological assays, showed antibacterial activity against six Gram-positive bacterial strains of standard S. aureus and clinical resistant S. aureus, and cytotoxicity tests presented promising in vitro antitumor activity against 4T1 cells (mouse breast metastatic adenocarcinoma) and B16F10 (murine metastatic melanoma), showing that the IC 50 obtained for the binuclear compound is around ten times more active than those found for cisplatin (reference drug).